A process evaluation of a Training of Trainers (TOT) model of men's health training. (25th July 2016) - Lefkowich, Maya; Richardson, Noel; Brennan, Lorcan; Lambe, Barry; Carroll, Paula
Abstract: This study set out to identify the mediators of diffusion of a Training of Trainers (ToT) programme; focusing on ENGAGE, Ireland's national men's health training programme, we explored the process (planning, implementation and maintenance) of using a ToT model of training to affect change in gender sensitive health and social service provision for men. Our findings indicate that an experiential learning approach in combination with mechanisms for feedback and fostering peer-based support during training and beyond are key strategies that foster individual (Trainer), community (of Trainers) and organizational (Trainer workplaces) level ownership. Moreover, by adapting in response to feedback, ENGAGE was able to remain relevant over a number years and to different cohorts of Trainers. As such, core strategies used by ENGAGE could be used to inform new models of health training elsewhere.